2022
DOI: 10.1155/2022/9455428
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation Combined with Repetitive Transcranial Magnetic Stimulation on Upper Limb Motor Function Rehabilitation in Stroke Patients with Hemiplegia

Abstract: Objective. To investigate the effect of neuromuscular electrical stimulation (NMES) combined with repetitive transcranial magnetic stimulation (rTMS) on upper limb motor dysfunction in stroke patients with hemiplegia. Methods. A total of 240 stroke patients with hemiplegia who met the inclusion criteria were selected and randomly divided into 4 groups (60 cases in each group): control group, NMES group, rTMS group, and NMES + rTMS group. Before treatment and 4 weeks after treatment, we evaluated and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In a subgroup analysis based on the rTMS method, a significant effect was noted in the rTMS group (21,26,28,33,34,36,59-62) (SMD, 0.48; 95% CI 0.21-0.76; P = 0.001) but not in TBS group (26,34,39,41,63) (SMD, 0.05; 95% CI −0.29-0.40; P = 0.76) (Supplementary Figure 4B and Table 2). Further, subgroup analysis based on rTMS frequency showed that 1 Hz rTMS (21,26,28,33,34,36,59-62) (SMD, 0.43; 95% CI 0.14-0.72; P = 0.004) produced better results than 3-10 Hz rTMS (33) (SMD, 0.23; 95% CI −0.59-1.06; P = 0.581) (Supplementary Figure 4C and Table 2).…”
Section: E Ect Of Rtms or Sham Stimulation On Fma-ue In Patients With...mentioning
confidence: 93%
See 3 more Smart Citations
“…In a subgroup analysis based on the rTMS method, a significant effect was noted in the rTMS group (21,26,28,33,34,36,59-62) (SMD, 0.48; 95% CI 0.21-0.76; P = 0.001) but not in TBS group (26,34,39,41,63) (SMD, 0.05; 95% CI −0.29-0.40; P = 0.76) (Supplementary Figure 4B and Table 2). Further, subgroup analysis based on rTMS frequency showed that 1 Hz rTMS (21,26,28,33,34,36,59-62) (SMD, 0.43; 95% CI 0.14-0.72; P = 0.004) produced better results than 3-10 Hz rTMS (33) (SMD, 0.23; 95% CI −0.59-1.06; P = 0.581) (Supplementary Figure 4C and Table 2).…”
Section: E Ect Of Rtms or Sham Stimulation On Fma-ue In Patients With...mentioning
confidence: 93%
“…Transcranial magnetic stimulation had a significant effect in patients with both severe baseline impairment (21,26,34,36,59,60,63) (SMD, 0.39; 95% CI 0.11-0.67; P = 0.006) and moderate baseline impairment (SMD, 0.34; 95% CI 0.03-0.65; P = 0.03) (Figure 2C and Table 2). In a subgroup analysis based on the rTMS method, a significant effect was noted in the rTMS group (21,26,28,33,34,36,59-62) (SMD, 0.48; 95% CI 0.21-0.76; P = 0.001) but not in TBS group (26,34,39,41,63) (SMD, 0.05; 95% CI −0.29-0.40; P = 0.76) (Supplementary Figure 4B and Table 2). Further, subgroup analysis based on rTMS frequency showed that 1 Hz rTMS (21,26,28,33,34,36,59-62) (SMD, 0.43; 95% CI 0.14-0.72; P = 0.004) produced better results than 3-10 Hz rTMS (33) (SMD, 0.23; 95% CI −0.59-1.06; P = 0.581) (Supplementary Figure 4C and Table 2).…”
Section: E Ect Of Rtms or Sham Stimulation On Fma-ue In Patients With...mentioning
confidence: 94%
See 2 more Smart Citations
“…As a non-invasive, safe, and easily accepted treatment technique, transcranial magnetic stimulation (TMS) has a wide effect on neural networks in the brain by altering the excitability of neurons [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%